Javanese and Batak Tribes: The Role of Moderation in Parenting Style on Self-Control in Adolscents - Sudirman, Dhiya Fauziyyah; Makruf, Herlin Asfarina; Rodiyah, Isyatin; Yuniardi, Muhammad Salis; Karmiyati, Diah (International Journal of Scientific Research and Management (IJSRM), 2024)
This research aims to determine the influence of parenting styles on self-control which is moderated by ethnicity in adolescents. The research design used is a correlational quantitative design. Sampling technique using method convenience sampling. The research used 2 scales, namely the Parental Style Inventory II (PSI-II) to measure parenting style and the Brief Self Control Scale to measure self-control. The data analysis technique in this research is using moderated regression analysis and simple regression tests. The research results show that ethnicity does not moderate the influence of parenting style on self-control (P Int_1 = 0.5323 > 0.05). Besides that, independent testing obtained significant results (parenting style influence self-control). However, when there is a covariate (another variable present), namely ethnicity and controlled simultaneously, it becomes insignificant (in the test using Hayes).